Membrane, pole piece, preparation method of pole piece, battery and electric equipment

By using soft sulfide solid electrolyte and hard active materials in all-solid state batteries, combined with high shear processing and hot rolling technology, the problem of poor fibrosis and strength of the diaphragm is solved, and a diaphragm with higher density and better performance is achieved.

CN119852312APending Publication Date: 2025-04-18CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410381194.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, the degree and strength of the diaphragm are poor, resulting in poor performance of all-solid-state batteries.

Method used

Using soft sulfide solid electrolytes and hard active materials, a high fibrosis diaphragm is formed through high shear processing and hot rolling technology to improve its tensile strength and flexibility.

Benefits of technology

It effectively improves the strength and flexibility of the diaphragm, forms a higher density diaphragm, and improves the performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852312A_ABST
    Figure CN119852312A_ABST
Patent Text Reader

Abstract

The invention discloses a diaphragm, a pole piece, a preparation method of the pole piece, a battery and electric equipment, the diaphragm comprises a sulfide solid electrolyte, an active material and a binder, the elastic modulus ESE of the sulfide solid electrolyte is less than 30 GPa, the shear modulus GSE of the sulfide solid electrolyte is less than 12 GPa, the sulfide solid electrolyte comprises Li and S, and the active material is an active material. The sulfide solid electrolyte further comprises at least one element of Sb, Sn, Te, Se, I and Br. According to the diaphragm and the sulfide solid electrolyte disclosed by the invention, the soft sulfide solid electrolyte is adopted, so that in the diaphragm containing the sulfide solid electrolyte and the active material, the binder can form high-degree fibrosis, and the formed strength after shearing is stronger and more uniform, thereby forming the diaphragm with excellent tensile strength and flexibility; the strength and the flexibility of the diaphragm are effectively improved, the diaphragm with higher compactness can be formed, and the performance of the diaphragm is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery manufacturing, and more specifically, to a diaphragm, a pole piece, a method for preparing the pole piece, a battery and an electrical device. Background Art

[0002] All-solid-state batteries use solid electrolytes to replace the electrolytes of traditional batteries. They are non-flammable and are therefore considered to be the next generation of high-safety batteries. Among them, sulfide solid electrolytes have high ionic conductivity and low grain boundary impedance, and have received widespread attention in the industry. Sulfide solid electrolytes will chemically react with strong polar solvents such as H2O and NMP (N-methylpyrrolidone), causing the structure of the sulfide solid electrolyte to be destroyed and lose its lithium conductivity, which causes certain problems in the preparation of electrode slurries based on sulfide solid electrolyte systems and wet coating.

[0003] In the prior art, the electrode is usually prepared by a solvent-free method. Under high shear conditions, a huge number of fibrous filaments are formed by the adhesive and intertwined with the solid electrolyte and active materials to form a membrane. For different inorganic particles in the dry film preparation process, the shear force required for the fiberization of the binder, the degree of fiberization of the binder after shearing, and the strength of the final membrane are all very different. Therefore, under the same conditions, it is of great significance to ensure the degree of fiberization of the binder and the strength of the membrane. Summary of the invention

[0004] One object of the present invention is to provide a new technical solution for a diaphragm, a pole piece, a method for preparing a pole piece, a battery and an electrical device, which can at least solve the problems of the diaphragm fiberization degree and poor strength in the prior art.

[0005] In a first aspect of the present invention, a membrane is provided, comprising a sulfide solid electrolyte, an active material and a binder, wherein the elastic modulus E of the sulfide solid electrolyte is SE <30GPa, the shear modulus G of the sulfide solid electrolyte SE <12GPa, the sulfide solid electrolyte includes Li and S, and the sulfide solid electrolyte also includes: at least one element of Sb, Sn, Te, Se, I, and Br.

[0006] Optionally, the elastic modulus E of the active material AM >100 GPa, the shear modulus of the active material G AM >50GPa.

[0007] Optionally, the active material is a positive electrode active material.

[0008] Optionally, the elastic modulus E of the sulfide solid electrolyte is SE<18GPa, the shear modulus G of the sulfide solid electrolyte SE <8GPa.

[0009] Optionally, the ratio of the elastic modulus of the sulfide solid electrolyte to the elastic modulus of the active material is 0.03<E SE / E AM <0.11, the ratio between the shear modulus of the sulfide solid electrolyte and the active material is 0.05<G SE / G AM <0.12.

[0010] Optionally, the ionic conductivity of the sulfide solid electrolyte is greater than 0.1 mS / cm.

[0011] Optionally, the ratio of the mass of the non-metallic elements in the sulfide solid electrolyte to the total mass of the sulfide solid electrolyte is greater than 15%.

[0012] A second aspect of the present invention provides a pole piece, comprising the membrane described in the above embodiment, and also comprising a current collector, wherein the membrane is arranged on at least one side of the current collector.

[0013] A third aspect of the present invention provides a method for preparing a pole piece, the method comprising:

[0014] The active material, the sulfide solid electrolyte, the binder and the conductive agent are mixed to form a mixed powder; wherein the elastic modulus E of the sulfide solid electrolyte is SE <30GPa, the shear modulus G of the sulfide solid electrolyte SE <12 GPa, the sulfide solid electrolyte includes Li and S, and the sulfide solid electrolyte also includes: at least one element of Sb, Sn, Te, Se, I, Br;

[0015] The mixed powder is subjected to a fiberization treatment under the action of a shear force to obtain a treated powder;

[0016] The treated powder is subjected to hot rolling to prepare a membrane;

[0017] The film is composited on the current collector by hot pressing to prepare a pole piece.

[0018] Optionally, the elastic modulus E of the active material AM >100 GPa, the shear modulus of the active material G AM >50GPa.

[0019] Optionally, the binder is one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyacrylic acid, polyacrylate, nitrile rubber, and styrene-butadiene rubber; the conductive agent is one or more of acetylene black, carbon nanotubes, carbon fibers, and carbon black.

[0020] Optionally, the shear force is generated by ball milling, air milling, kneading, screw extrusion, high-speed dispersion, degassing or ultrasound.

[0021] Optionally, the hot rolling temperature is 120°C to 230°C.

[0022] A fourth aspect of the present invention provides a battery, comprising the pole piece described in the above embodiment, wherein the pole piece is manufactured using the pole piece manufacturing method described in the above embodiment.

[0023] A fifth aspect of the present invention provides an electrical device comprising the battery described in the above embodiment.

[0024] The diaphragm of the present invention adopts a soft sulfide solid electrolyte as the sulfide solid electrolyte, ensuring that the binder in the diaphragm containing the sulfide solid electrolyte and the active material can form a high degree of fiberization, and the strength of the formed film after shearing is stronger and more uniform, thereby forming a diaphragm with excellent tensile strength and flexibility, effectively improving the strength and flexibility of the diaphragm, and being conducive to forming a diaphragm with higher density, thereby improving the performance of the diaphragm.

[0025] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0027] Figure 1 4 is a flow chart of a method for preparing a pole piece according to an embodiment of the present invention. DETAILED DESCRIPTION

[0028] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.

[0029] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.

[0030] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.

[0031] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0032] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0033] In the specification and claims of the present invention, if the term "first" or "second" is involved, it may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more. In addition, "and / or" in the specification and claims means at least one of the connected objects, and the character " / " generally means that the related objects are in an "or" relationship.

[0034] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation to the present invention.

[0035] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installation", "connection" and "connection" involved should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0036] The following describes in detail the diaphragm according to the embodiment of the present invention with reference to the accompanying drawings.

[0037] The membrane according to an embodiment of the present invention includes a sulfide solid electrolyte, an active material and a binder, wherein the elastic modulus E of the sulfide solid electrolyte is SE<30GPa, the shear modulus G of the sulfide solid electrolyte SE <12GPa, the sulfide solid electrolyte includes Li and S, and the sulfide solid electrolyte also includes: at least one element of Sb, Sn, Te, Se, I, and Br.

[0038] In other words, the membrane according to the embodiment of the present invention is mainly composed of a sulfide solid electrolyte and an active material, wherein the sulfide solid electrolyte adopts a soft solid electrolyte. In the dry film making process, after the binder powder and the solid electrolyte and the active material are mixed, the binder is formed into a huge number of fibrous filaments under high shear conditions and intertwined with the electrolyte and the active material, and then a membrane is formed by rolling or the like. However, in the dry film making process for different inorganic particles (with different degrees of hardness and softness), the shear force required for the fiberization of the binder and the degree of fiberization after shearing will cause a great difference in the strength of the film. For the current sulfide solid electrolyte and active material system, dry film making has problems such as difficulty in film making and low film strength.

[0039] The sulfide solid electrolyte of the present invention can be a soft solid electrolyte, which can achieve sufficient fiberization of the binder, so that the prepared membrane has the characteristics of excellent tensile strength and good flexibility. The soft solid electrolyte here refers to the elastic modulus E SE <30GPa type, and shear modulus G SE Solid electrolyte with a temperature of <12GPa. During the fiberization stage of the pole piece, the particles of the sulfide solid electrolyte will be refined to a certain extent under the action of high shear force. The smaller particle size makes it easier to fill the gaps between the composite active materials during the later molding and compaction process. In addition, the characteristics of the soft sulfide solid electrolyte, such as low elastic modulus, high fiberization degree of the pole piece, and high flexibility, are conducive to the formation of a more compact and stable electrode structure, which is conducive to the conduction of Li ions in the composite membrane and the improvement of the performance of the electrode and battery.

[0040] According to one embodiment of the present invention, the elastic modulus E of the active material AM >100 GPa, the shear modulus of the active material G AM >50GPa. The active material of the present invention can be a hard active material, which can ensure that the original state of the active material is maintained during the fiberization process without being damaged by shear force, thereby maintaining the stable performance of its performance. The hard active material here refers to the elastic modulus E AM >100GPa, shear modulus G AM Active material types >50GPa.

[0041] Therefore, according to the diaphragm of the embodiment of the present invention, the sulfide solid electrolyte adopts a soft solid electrolyte, and the active material adopts a hard active material, ensuring that the sulfide solid electrolyte and the active material can form a high degree of fiberization during the fiberization process, and the strength of the formed part after shearing is stronger and more uniform, thereby forming a diaphragm with excellent tensile strength and flexibility, effectively improving the strength and flexibility of the diaphragm, and being conducive to forming a diaphragm with higher density, thereby improving the performance of the diaphragm.

[0042] According to one embodiment of the present invention, the elastic modulus E of the sulfide solid electrolyte SE <18GPa, shear modulus G of sulfide solid electrolyte SE <8GPa. In other words, the elastic modulus E of the sulfide solid electrolyte SE <18GPa, shear modulus G of sulfide solid electrolyte SE <8GPa. Optionally, the elastic modulus E of the sulfide solid electrolyte SE <18GPa, shear modulus G of sulfide solid electrolyte SE <7GPa. During the fiberization stage of the sulfide sulfide solid electrolyte, the particles will be refined to a certain extent under the action of high shear force. The smaller particle size is convenient for better filling the gaps between the composite positive electrode particles during the later molding and compaction process. In addition, the low elastic modulus, high fiberization degree of the pole piece, and high flexibility of the sulfide solid electrolyte are further conducive to the formation of a denser electrode structure, which is conducive to the conduction of Li ions in the composite positive electrode and the improvement of the performance of the electrode and battery.

[0043] According to one embodiment of the present invention, the ratio between the elastic modulus of the sulfide solid electrolyte and the active material is 0.03 < E SE / E AM <0.11, the ratio between the shear modulus of the sulfide solid electrolyte and the active material is 0.05<G SE / G AM <0.12.

[0044] In other words, the ratio between the elastic modulus of the sulfide solid electrolyte and the active material can satisfy 0.03<E SE / E AM <0.11, the ratio between the shear modulus of the sulfide solid electrolyte and the active material can satisfy 0.05<G SE / G AM <0.12, further ensuring that the membrane maintains excellent properties in both mechanical and electrochemical properties.

[0045] According to one embodiment of the present invention, the ionic conductivity of the sulfide solid electrolyte is greater than 0.1mS / cm. In other words, the ionic conductivity σi of the sulfide solid electrolyte is selected from the system of σi>0.1mS / cm. Alternatively, the system of σi>1mS / cm, preferably, the system of σi>5mS / cm. The present invention can further optimize the electrochemical performance of the membrane by selecting a system of high ionic conductivity in a sulfide solid electrolyte of low elastic modulus and low hardness type.

[0046] In some specific embodiments of the present invention, the ratio of the mass of the non-metallic elements in the sulfide solid electrolyte to the total mass of the sulfide solid electrolyte is greater than 15%.

[0047] The composition of the sulfide solid electrolyte includes not only essential elements such as Li and S, but also soft elements, which refer to one or more long-period non-metallic or semi-metallic elements including Sb, Sn, Te, Se, I, Br, etc. The ratio of the mass of the soft element to the total mass of the electrolyte is greater than 15%, and preferably greater than 25%.

[0048] The present invention adopts a soft sulfide solid electrolyte and a hard active material to prepare a composite electrode plate. Starting from the element composition of the sulfide solid electrolyte, the elastic modulus of the sulfide solid electrolyte is optimized. The proportional relationship between the elastic modulus of the sulfide solid electrolyte and the elastic modulus of the active material is limited, so that the elastic modulus and shear modulus of the soft sulfide solid electrolyte and the hard active material meet 0.03<E SE / E AM <0.11,0.05<G SE / G AM <0.12, and finally a sulfide solid-state battery dry-process electrode with excellent tensile strength and good flexibility is prepared to achieve good performance of the solid-state battery.

[0049] In the present invention, the sulfide solid electrolyte can be 70Li2S-20P2S5-10LiI, Li 6-x PS 5-x Br 1+x (0≤X≤1), Li6SbS5I, Li7PS6Se 6-Y (0≤X≤4), etc.

[0050] In the present invention, the active material includes a positive electrode active material. The positive electrode active material has a higher hardness and is more suitable for the system in the present invention.

[0051] The positive electrode active material can be olivine, such as LiFePO4, etc. It can also be layered oxides, such as NCM, NCA or LiCoO2, etc. It can also be spinel, such as LiMn2O4, Li4Ti5O12 Etc. Soft sulfide solid electrolytes are paired with dry binders, and it is easier to achieve fiberization of dry binders under high shear conditions, so that the strength and flexibility of the membrane are improved. The characteristics of soft sulfide solid electrolytes can be achieved by limiting the elemental composition of the electrolyte. During the fiberization process, the electrolyte particles can be further reduced, and combined with its low elastic modulus characteristics and the flexibility of the membrane, a higher density can be achieved after pressing. The high modulus active material can ensure that it maintains its original state during the fiberization process without being destroyed by shear force, thereby maintaining the stability of its performance.

[0052] In summary, the diaphragm according to the embodiment of the present invention adopts a soft solid electrolyte to ensure that the diaphragm can form a high degree of fiberization, and the strength of the formed part after shearing is stronger and more uniform, thereby forming a diaphragm with excellent tensile strength and flexibility, effectively improving the strength and flexibility of the electrode, and facilitating the formation of a higher density diaphragm, thereby improving the performance of the diaphragm.

[0053] According to a second aspect of the present invention, there is provided a pole piece, comprising the membrane described in the above embodiment, the pole piece further comprising a current collector, and the membrane is arranged on at least one side of the current collector.

[0054] In other words, since the diaphragm according to the embodiment of the present invention has the above-mentioned technical effects, the pole piece according to the embodiment of the present invention should also have the corresponding technical effects. Specifically, the diaphragm in the pole piece of the present invention is mainly composed of a sulfide solid electrolyte and an active material, wherein the sulfide solid electrolyte adopts a soft solid electrolyte. In the dry film making process, after the binder powder and the solid electrolyte and the active material are mixed, under high shear conditions, the binder forms a huge number of fibrous filaments and intertwines with the electrolyte and the active material, and then forms a diaphragm by rolling and the like. However, in the dry film making process for different inorganic particles (with different degrees of hardness and softness), the shear force required for the fiberization of the binder and the degree of fiberization after shearing will cause a great difference in the strength of the film. As far as the current sulfide solid electrolyte and active material system is concerned, dry film making has problems such as difficulty in film making and low film strength.

[0055] The membrane of the present invention can be arranged on at least one side of the current collector, and the pole piece made by using the membrane, wherein the sulfide solid electrolyte can be a soft solid electrolyte, can achieve full fiberization of the binder, which is beneficial to increase the bonding force between the membrane and the current collector. The soft solid electrolyte here refers to the elastic modulus E SE <30GPa Type shear modulus G SESolid electrolyte with a temperature of <12GPa. During the fiberization stage of the pole piece, the particles of the sulfide solid electrolyte will be refined to a certain extent under the action of high shear force. The smaller particle size makes it easier to fill the gaps between the composite active materials during the later molding and compaction process. In addition, the characteristics of the soft sulfide solid electrolyte, such as low elastic modulus, high fiberization degree of the pole piece, and high flexibility, are conducive to the formation of a more compact and stable electrode structure, which is conducive to the conduction of Li ions in the pole piece and the improvement of the performance of the electrode and battery.

[0056] Therefore, according to the diaphragm of the embodiment of the present invention, the sulfide solid electrolyte adopts a soft solid electrolyte, and the active material adopts a hard active material, ensuring that the sulfide solid electrolyte and the active material can form a high degree of fiberization during the fiberization process, and the strength of the molding after shearing is stronger and more uniform, thereby forming a pole piece with excellent tensile strength and flexibility, effectively improving the strength and flexibility of the pole piece, and being conducive to forming a pole piece with higher density, thereby improving the performance of the pole piece.

[0057] According to a third aspect of the present invention, a method for preparing a pole piece is provided, the method comprising:

[0058] S1. Mixing active materials, solid electrolytes, adhesives and conductive agents to form mixed powders; wherein the elastic modulus E of the sulfide solid electrolyte is SE <30GPa, the shear modulus G of the sulfide solid electrolyte SE <12GPa, the sulfide solid electrolyte includes Li and S, and the sulfide solid electrolyte also includes: at least one element of Sb, Sn, Te, Se, I, and Br.

[0059] S2, subjecting the mixed powder to a fiberization treatment under the action of a shear force to obtain a treated powder;

[0060] S3, hot rolling the treated powder to prepare a membrane;

[0061] S4. Composite the membrane onto the current collector by hot pressing to prepare a pole piece.

[0062] In other words, the preparation method of the present invention adopts a dry film making method. Since the sulfide solid electrolyte will react chemically with high polarity solvents such as H2O and NMP (N-methylpyrrolidone), the structure will be destroyed and the lithium conductivity will be lost. In the wet pulping process, even if a low-polarity or non-polar solvent is used and matched with a corresponding binder, the low-polarity, non-protonic solvent will slow down the damage to the sulfide solid electrolyte structure to a certain extent, but it is impossible to completely avoid the adverse reaction between the solvent and the electrolyte. In fact, even if such a solvent is used to prepare a sulfide solid electrolyte slurry, the attenuation of the ionic conductivity of the electrolyte is still obvious. It will still affect the quality of the pole piece and the electrolyte membrane, and then affect the performance of the battery.

[0063] The present invention adopts a dry preparation method, and the sulfide solid electrolyte can adopt a soft solid electrolyte, which can achieve sufficient fiberization of the binder, so that the prepared electrode has the characteristics of excellent tensile strength and good flexibility. Among them, the sulfide solid electrolyte can adopt an elastic modulus E SE <30GPa, shear modulus G SE Solid electrolyte with a capacity of less than 12GPa. During the fiberization stage of the electrode, the particles of sulfide solid electrolyte will be refined to a certain extent under the action of high shear force. The smaller particle size is convenient for better filling the gaps between the composite positive electrode particles during the later molding and compaction process. In addition, the high fiberization degree and high flexibility of the electrode are conducive to the formation of a denser electrode structure, which is conducive to the conduction of Li ions in the composite positive electrode and the improvement of the performance of the electrode and battery.

[0064] The sulfide solid electrolyte of the present invention contains not only essential elements such as Li and S, but also soft elements, wherein the soft elements refer to one or more long-period non-metal or semi-metal elements including Sb, Sn, Te, Se, I, Br, etc.

[0065] The active material used in the present invention can be of elastic modulus E AM >100GPa active materials, the active materials can use the shear modulus G AM >50GPa active materials. Hard active materials with high elastic modulus and high shear modulus can ensure that they maintain their original state during the fiberization process without being destroyed by shear force, thereby maintaining their stable performance.

[0066] In the preparation method of the present invention, first, the active material, the sulfide solid electrolyte, the adhesive and the conductive agent can be mixed to form a mixed powder. Then, the mixed powder can be subjected to a fiberization treatment under the action of a shear force to obtain a treated powder, and then the treated powder can be subjected to a hot rolling treatment to prepare a membrane. Finally, the membrane can be composited on a current collector by hot pressing to prepare a pole piece, which is a positive pole piece.

[0067] The present invention uses a soft sulfide solid electrolyte and an active material to prepare a dry-process electrode. This powder combination is used in the dry-process film-making process, which makes it easier to achieve sufficient fiberization of the binder, so that the prepared electrode has the characteristics of excellent tensile strength and good flexibility.

[0068] Therefore, the preparation method of the pole piece according to the embodiment of the present invention can ensure that the sulfide solid electrolyte and the active material can form a high degree of fiberization during the fiberization process, and the strength of the formed part after shearing is stronger and more uniform, thereby forming a pole piece with excellent tensile strength and flexibility, effectively improving the strength and flexibility of the pole piece, and facilitating the formation of a higher density pole piece, thereby improving the performance of the pole piece.

[0069] According to one embodiment of the present invention, the elastic modulus E of the active material AM >100GPa, shear modulus of active material G AM >50GPa. The active material of the present invention can be a hard active material, which can ensure that the original state of the active material is maintained during the fiberization process without being damaged by shear force, thereby maintaining the stable performance of its performance. The hard active material here refers to the elastic modulus E AM >100GPa, shear modulus G AM Active material types >50GPa.

[0070] According to one embodiment of the present invention, the binder is one or more of PTFE, PVDF, PAA, polyacrylate, NBR, and SBR, ensuring that the binder can effectively achieve fiberization. The conductive agent is one or more of acetylene black, carbon nanotubes, carbon fibers, and carbon black.

[0071] According to one embodiment of the present invention, the shear force is generated by ball milling, air milling, kneading, screw extrusion, high-speed dispersion, degassing or ultrasound, which is simple and easy to operate.

[0072] According to one embodiment of the present invention, the hot rolling temperature is 120° C. to 230° C., which is conducive to hot rolling thinning of the high shear treated powder.

[0073] In the present invention, the fiberization degree of the binder after high shearing of the mixed powder can be compared by SEM (scanning electron microscope) observation to statistically analyze the diameter and number of the binder fibers. The information of the elastic modulus and shear modulus can be tested by a nanoindenter. The tensile strength of the pole piece can be tested by a tensile testing machine.

[0074] Specifically, the present invention can characterize the electrochemical properties of the electrode through a powder-type half-cell, and the counter electrode can be a lithium-indium alloy. The specific preparation method is: first cut the prepared pole piece and lithium-indium alloy sheet into small discs of φ15 mm respectively. Weigh 200 mg of electrolyte powder in a glove box with an argon atmosphere, and use a φ15 mm mold to press it into an electrolyte sheet at 120 MPa. Add an electrode disc to one side of the electrolyte sheet, apply a pressure of 380 MPa as the working electrode, and put a lithium-indium alloy sheet on the other side as the counter electrode to assemble into a half-cell. The mold battery assembled by the above method was subjected to constant current charge and discharge test using the Landian multi-channel charge and discharge test system (LAND CT2001A).

[0075] The method for preparing the pole piece of the present invention is described below in conjunction with a specific implementation.

[0076] Example 1

[0077] Elastic modulus test:

[0078] (1) Select LiNi 0.9 Co 0.05 Mn 0.05 O2 as active material, Li6PS5Cl 0.5 Br 0.5 As a solid electrolyte. Weigh Li6PS5Cl 0.5 Br 0.5 200 mg of electrolyte powder was pressed into small discs in a φ15 mm tungsten carbide mold at a pressure of 600 MPa. The elastic modulus and shear modulus were tested using a nanoindenter.

[0079] (2) Preparation of dry membrane:

[0080] Accurately weigh the active positive electrode LiNi 0.9 Co 0.05 Mn 0.05 O2, sulfide solid electrolyte Li6PS5Cl 0.5 Br 0.5 80g, 20g, 1.5g, 0.5g of binder PTFE (polytetrafluoroethylene), and conductive agent Sup P were placed in a zirconia-lined ball mill with 100g of zirconia ball milling beads. The mixture was uniformly mixed and sheared for 1 hour using a ball mill at a speed of 400RPM.

[0081] Then, the high-speed sheared and evenly mixed powder is hot-rolled by a hot roller press to form a 600um thick film, and then further hot-rolled to thin the film to 100um to obtain the desired film. The hot rolling temperature used in this process is 145°C.

[0082] (3) Diaphragm tensile strength test:

[0083] The membrane obtained in part (2) was cut into a rectangle with a width of 4 cm and a length of 7 cm, and the tensile strength of the membrane was tested using a universal tensile testing machine.

[0084] (4) Film peeling force test:

[0085] Take the membrane obtained in part (2), and use a hot roller press heated at 90° C. to composite the membrane on a carbon-coated aluminum foil current collector to obtain a dry-process electrode, and use a peel force tester to test the electrode peel force.

[0086] (5) Electrochemical performance test of electrode:

[0087] Take the membrane prepared in part (2) and prepare the electrode using the same method as (4). Cut the prepared electrode and lithium-indium alloy sheet into small discs of φ15 mm respectively. Weigh 200 mg of electrolyte powder in a glove box with argon atmosphere and use a φ15 mm mold to press it into an electrolyte sheet at 120 MPa. Add the electrode disc to one side of the electrolyte sheet and apply a pressure of 380 MPa as the working electrode. Put the lithium-indium alloy sheet on the other side as the counter electrode to assemble into a half-cell. Use the Landian multi-channel charge and discharge test system (LAND CT2001A) to perform constant current charge and discharge tests on the mold battery assembled by the above method to obtain the electrochemical properties of the electrode.

[0088] Example 2

[0089] Same as Example 1, except that the electrolyte 70Li2S-20P2S5-10LiI is used instead of the electrolyte Li6PS5Cl 0.5 Br 0.5 .

[0090] Example 3

[0091] Same as Example 1, except that the electrolyte Li 6.4 Ge 0.4 Sb 0.6 S5I replaces Li6PS5Cl electrolyte 0.5 Br 0.5 .

[0092] Example 4

[0093] Same as Example 1, except that the active positive electrode LiCoO2 is used instead of the active positive electrode LiNi 0.9 Co 0.05 Mn 0.05 O2.

[0094] Example 5

[0095] Same as Example 1, except that the active positive electrode LiCoO2 is used instead of the active positive electrode LiNi0.9 Co 0.05 Mn 0.05 O2. Using electrolyte Li 6.7 Si 0.7 Sb 0.3 S5I replaces Li6PS5Cl electrolyte 0.5 Br-0 . 5.

[0096] Example 6

[0097] Same as Example 1, except that the active positive electrode LiCoO2 is used instead of the active positive electrode LiNi 0.9 Co 0.05 Mn 0.05 O2. Using electrolyte Li6PS 3.7 Se 1.3 Br replaces electrolyte Li6PS5Cl 0.5 Br-0 . 5.

[0098] Example 7

[0099] The same as Example 1, the only difference is that the amount of PTFE added is 2.5%, and the electrolyte Li is used. 5.3 PS 4.3 ClBr 0.7 Replace electrolyte Li6PS5Cl 0.5 Br 0.5 .

[0100] Example 8

[0101] Same as Example 1, except that the active positive electrode LiCoO2 is used instead of the active positive electrode LiNi 0.9 Co 0.05 Mn 0.05 O2, electrolyte Li 10 SnP2S 12 Replace electrolyte Li6PS5Cl 0.5 Br 0.5 .

[0102] Example 9

[0103] Same as Example 1, except that the electrolyte Li 10 SnP2S 12 Replace electrolyte Li6PS5Cl 0.5 Br 0.5 .

[0104] Example 10

[0105] Same as Example 1, except that the active positive electrode LiNi 0.6 Co0.2 Mn 0.2 O2 is a very suitable material for lithium manganese iron phosphate, replacing the active positive electrode LiNi 0.9 Co 0.05 Mn 0.05 O2; at the same time, the binder content is 2.5%, while reducing the corresponding amount of positive electrode material.

[0106] Comparative Example 1

[0107] Same as Example 1, except that electrolyte Li6PS5Cl is used instead of electrolyte Li6PS5Cl 0.5 Br 0.5 .

[0108] Comparative Example 2

[0109] Same as Example 1, except that active positive electrode LiCoO2 is used instead of active positive electrode LiNi 0.9 Co 0.05 Mn 0.05 O2, using electrolyte Li2SiS3 instead of electrolyte Li6PS5Cl 0.5 Br 0.5 .

[0110] At the same time, the present invention has carried out a series of performance characterization tests according to various embodiments and comparative examples, wherein Table 1 is E SE 、E AM , G SE , G AM Tests, Table 2 is the tensile strength of the electrode, the deformation at the maximum force point, and the electrode peeling force test, and Table 3 is the performance test of the positive electrode to prepare the battery.

[0111] Table 1 is E SE 、E AM , G SE , G AM test:

[0112]

[0113]

[0114] Table 2 shows the pole piece tensile strength, maximum force point deformation, and pole piece peeling force test:

[0115] Tensile strength / MPa Maximum force point deformation / mm Pole peeling force / N / 40mm Example 1 1.12 6.24 0.75 Example 2 1.28 6.22 0.89 Example 3 1.46 7.18 1.07 Example 4 1.24 6.14 0.72 Example 5 1.27 6.85 0.92 Example 6 1.11 6.23 0.77 Example 7 1.49 8.01 0.79 Example 8 1.01 5.54 0.65 Example 9 1.03 5.09 0.69 Example 10 2.01 5.95 0.70 Comparative Example 1 0.78 4.40 0.54 Comparative Example 2 0.55 1.97 0.40

[0116] Table 3 Performance test of battery prepared by positive electrode sheet:

[0117]

[0118]

[0119] As can be seen from Table 1, Table 2 and Table 3, the present invention uses a soft sulfide solid electrolyte and is used in combination with an active material to prepare a dry-process electrode. This powder combination is used in the dry-process film-making process, which makes it easier to fully fiberize the binder, so that the prepared electrode has the characteristics of excellent tensile strength and good flexibility. The sulfide solid electrolyte and the active material can form a high degree of fiberization during the fiberization process, and the strength of the formed material after shearing is stronger and more uniform, thereby forming a electrode with excellent tensile strength and flexibility, effectively improving the strength and flexibility of the electrode, and is conducive to forming a higher density electrode, improving the performance of the electrode and the battery.

[0120] Therefore, the present invention adopts a dry preparation method, the sulfide solid electrolyte can be a soft solid electrolyte, and the active material can be a hard active material, which can achieve full fiberization of the binder, so that the prepared electrode has the characteristics of excellent tensile strength and good flexibility. Among them, the solid electrolyte can be a soft solid electrolyte with an elastic modulus E SE <30GPa type solid electrolyte, solid electrolyte can use shear modulus G SE Solid electrolyte with elastic modulus E AM >100GPa active materials, the active materials can use the shear modulus G AM >50GPa active materials. During the fiberization stage of the electrode sheet, the particles of the sulfide solid electrolyte will be refined to a certain extent under the action of high shear force. The smaller particle size is convenient for better filling the gaps between the composite positive electrode particles during the later molding and compaction process. In addition, the low elastic modulus, high fiberization degree of the electrode sheet, and high flexibility of the sulfide solid electrolyte are conducive to the formation of a denser electrode structure, which is conducive to the conduction of Li ions in the composite positive electrode and the improvement of the performance of the electrode and battery. The active materials with high elastic modulus and high shear modulus can ensure that they remain in their original state during the fiberization process without being destroyed by shear force, thereby maintaining the stability of their performance.

[0121] According to a fourth aspect of the present invention, a battery is provided, comprising the pole piece in the above embodiment, wherein the pole piece is prepared by the pole piece preparation method in the above embodiment. Since the pole piece prepared by the above preparation method according to the embodiment of the present invention has the above technical effect, the battery according to the embodiment of the present invention should also have the corresponding technical effect, that is, the battery according to the embodiment of the present invention adopts the pole piece, which can effectively improve the performance of the battery.

[0122] Of course, for those skilled in the art, other structures and working principles of the battery are understandable and achievable, and will not be described in detail in the present invention.

[0123] According to a fifth aspect of the embodiments of the present invention, there is provided an electric device, comprising the battery in the above embodiments. Since the battery according to the embodiments of the present invention has the above technical effects, the electric device according to the embodiments of the present invention should also have corresponding technical effects, that is, the electric device according to the embodiments of the present invention adopts the electrode piece, which can effectively improve the endurance of the electric device.

[0124] Of course, for those skilled in the art, other structures and working principles of the electrical equipment are understandable and achievable, and will not be described in detail in the present invention.

[0125] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.

Claims

1. A diaphragm, characterized in that: The present invention comprises a sulfide solid electrolyte, an active material and a binder, wherein the elastic modulus E of the sulfide solid electrolyte is SE <30GPa, the shear modulus G of the sulfide solid electrolyte SE <12GPa, the sulfide solid electrolyte includes Li and S, and the sulfide solid electrolyte also includes: at least one element of Sb, Sn, Te, Se, I, and Br.

2. The diaphragm according to claim 1, characterized in that The elastic modulus E of the active material AM >100 GPa, the shear modulus of the active material G AM >50GPa.

3. The diaphragm according to claim 1, characterized in that The active material is a positive electrode active material.

4. The diaphragm according to claim 1, characterized in that The elastic modulus E of the sulfide solid electrolyte SE <18GPa, the shear modulus G of the sulfide solid electrolyte SE <8GPa.

5. The diaphragm according to claim 2, characterized in that The ratio between the elastic modulus of the sulfide solid electrolyte and the active material is 0.03<E SE / E AM <0.11, the ratio between the shear modulus of the sulfide solid electrolyte and the active material is 0.05<G SE / G AM <0.

12.

6. The diaphragm according to claim 1, characterized in that The ionic conductivity of the sulfide solid electrolyte is greater than 0.1 mS / cm.

7. The diaphragm according to claim 1, characterized in that The ratio of the mass of the non-metallic elements in the sulfide solid electrolyte to the total mass of the sulfide solid electrolyte is greater than 15%.

8. A pole piece, characterized in that: The invention comprises the membrane as claimed in any one of claims 1 to 7, and further comprises a current collector, wherein the membrane is arranged on at least one side of the current collector.

9. A method for preparing a pole piece, characterized in that: The preparation method comprises: The active material, the sulfide solid electrolyte, the binder and the conductive agent are mixed to form a mixed powder; wherein the elastic modulus E of the sulfide solid electrolyte is SE <30GPa, the shear modulus G of the sulfide solid electrolyte SE <12 GPa, the sulfide solid electrolyte includes Li and S, and the sulfide solid electrolyte also includes: at least one element of Sb, Sn, Te, Se, I, Br; The mixed powder is subjected to a fiberization treatment under the action of a shear force to obtain a treated powder; The treated powder is subjected to hot rolling to prepare a membrane; The film is composited on the current collector by hot pressing to prepare a pole piece.

10. The method for preparing a pole piece according to claim 9, characterized in that: The elastic modulus E of the active material AM >100 GPa, the shear modulus of the active material G AM >50GPa.

11. The method for preparing a pole piece according to claim 9, characterized in that: The binder is one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyacrylic acid, polyacrylate, nitrile rubber, and styrene-butadiene rubber; the conductive agent is one or more of acetylene black, carbon nanotubes, carbon fibers, and carbon black.

12. The method for preparing a pole piece according to claim 9, characterized in that: The shear force is generated by ball milling, air milling, kneading, screw extrusion, high-speed dispersion, degassing or ultrasound.

13. The method for preparing a pole piece according to claim 9, characterized in that: The hot rolling temperature is 120°C to 230°C.

14. A battery, characterized in that: It includes the pole piece as claimed in claim 8, wherein the pole piece is made by the method for making the pole piece as claimed in any one of claims 9 to 13.

15. An electrical equipment, characterized in that: Comprising the battery of claim 14.

Citation Information

Cited By

  • Dry-method solid electrolyte layer for battery, preparation method of dry-method solid electrolyte layer and solid-state battery

    CN120511349A